PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. TELKOM BIMA - Feni Aryanti, Ikbal Irawan (Journal of Mandalika Literature, 2021)
This study aims to analyze the effect of occupational safety and health on the work productivity of employees at PT Telkom Bima. This research is an associative type of research. The population in this study was all permanent employees as many as 33 respondents. the sample used in this study was purposive sampling. The research instrument uses a questionnaire with a likert scale. Data analysis uses multiple linear regression, correlation test, determination test, t test (partial) and f test (simultaneous). The results of the study based on the t test (partial) showed that safety does not affect work productivity, occupational health affects work productivity, while safety and health affect together affect work productivity.